The Role Of Investigators In Criminal Acts Of Umrah Scam - Wirnangsi Puluhulawa; Mohamad Rusdiyanto Puluhulawa; Novendri M. Nggilu; Apripari Apripari (Estudiante Law Journal, 2022)
The research objective is to find out the role of investigators in the umrah scam in Gorontalo and the factors causing the umrah scam in Gorontalo. The method used in this current research is empirical legal research. The research findings show that the Umrah scam cases in Gorontalo increase in, and they are not only committed by unlicensed travel agencies but also those who have obtained permits. There are various forms of scam, ranging from cancellation of departure, abandonment of pilgrims to promise breaking of Umrah travel service providers so that pilgrims experience disappointment. In this case, there has been an increasing number of detrimental cases against Umrah pilgrims, including in Gorontalo. In addition, the factors that cause hajj and umrah travel scam are divided into several types including: factors originating from the perpetrator, family factor, economic factor, environmental factor, cultural factor, and community factor or victims. In the meantime, the roles of police or investigators in dealing with hajj and umrah travel scam are to conduct examination of potential suspects and witnesses who corroborate a report, and conduct a review of the scene of the case after having a strong testimony from witnesses and then carry out an investigation. Also, the police’s efforts are to enlighten and do socialization from the Ministry of Religious Affairs and the people related to the office regarding the list of travel that has a permit as an Umrah Travel Organizer.